Everolimus and Long-term Clinical Outcomes in Kidney Transplant Recipients: A Registry-based 10-year Follow-up of 5 Randomized Trials. Issue 8 (August 2019) - Ying, Tracey; Wong, Germaine; Lim, Wai H.; Clayton, Philip; Kanellis, John; Pilmore, Helen; Campbell, Scott; O'Connell, Philip J.; Russ, Graeme; Chadban, Steven
Abstract : Background: Data regarding the long-term efficacy of everolimus-based immunosuppression for kidney transplantation are lacking. Existing randomized controlled trials are limited by short follow-up duration which limits capacity to assess impact on graft and patient survival. Methods: We linked individual trial participants to the Australian and New Zealand Dialysis and Transplant Registry. Using a 1-step meta-analysis approach, we investigated the 10-year risk of graft loss, mortality and graft function in 349 participants from 5 randomized trials of everolimus-based immunosuppression. Results: Two hundred forty-two patients randomized to everolimus and 107 control patients were followed for a median of 9 years (interquartile range, 7.1, 9.8 y). There were no significant differences in the risk of all-cause graft loss (adjusted hazard ratio [HR], 1.16; 95% confidence interval [CI], 0.69-1.94), mortality (adjusted HR, 1.51; 95% CI, 0.78-2.93) and death-censored graft loss in everolimus versus control (adjusted HR, 1.00; 95% CI, 0.50-2.01). For patients in the early initiation (de novo or <6-month conversion) everolimus trials (n = 279), decline in estimated glomerular filtration rate did not significantly differ with control (mean difference in the slope of estimated glomerular filtrate rate, 0.01 mL/min per 1.73 m 2 [−0.06 to +0.09]). Conclusions: This registry-based analysis with long-term follow-up found no differences in graft and recipient survival or graft function for everolimus over current standard of care. Abstract : Supplemental Digital Content is available in the text.